Simulation of the Effective Distribution of Biofuel Droplets in a Reacting Flow - Aliya Askarova; Saltanat Bolegenova; Shynar Ospanova; Karlygash Bolegenova; Alfiya Nurmukhanova (Journal of Machine Engineering)
This work is devoted to developing a universal model of atomization and combustion of biofuel droplets using a statistical approach and a particle trajectory tracking model. The model applies to all types of biodiesel used in internal combustion engines with direct injections and is designed to optimize combustion processes, reduce emissions, and improve engine efficiency. Based on mathematical equations of conservation of mass, momentum, and energy, as well as numerical methods for calculating complex turbulent flows and the droplet atomization process, complex computational experiments were carried out using modern technologies. Research has shown that biodiesel has higher combustion temperatures and better evaporation characteristics compared to diesel fuel, which helps to reduce carbon oxides and soot emissions. The results of modeling the effect of pressure in the combustion chamber on the combustion process showed that its increase reduces soot emissions and promotes more complete fuel combustion. Visualization of aerodynamic and temperature profiles confirms the high efficiency of biodiesel combustion, especially under high temperature and pressure conditions.